Influence of the Instagram-Assisted Flipped Classroom Learning Model on Students' Mathematical Communication at Middle School - Saferlin, Dian; Badu, Syamsu Qamar; Zakaria, Perry; Kobandaha, Putri Ekawati (ETDC: Indonesian Journal of Research and Educational Review, 2025)
It is important for schools to improve students' mathematical communication. However, a preliminary study at Public Middle School 1 Bulango Selatan revealed that some students still struggle to solve problems given by the teacher, particularly those related to determining the length of a side of a flat shape, especially in the context of congruence and similarity. Therefore, the intent of this study was to determine the effect of the flipped classroom learning model assisted by Instagram on students' mathematical communication at Public Middle School 1 Bulango Selatan. The method used in this study was an experimental method consisting of an experimental class and a control class with a research design used, namely a post-test-only group design. We conducted a t-test data analysis on both the experimental and control classes. The findings of the study showed that the t-count was greater than the t-table value; specifically, the t-count was 2.083, which is greater than 2.042, leading to the rejection of H0. Thereby, it can be concluded that learning using the flipped classroom learning model on the material of congruence and similarity of flat shapes can affect students' mathematical communication skills.